Can Hot and Cold Slabs Transport Water Into the Deep Mantle Beyond Subduction Zone Magmatism? - Julia M. Ribeiro; Jeff Ryan; Jonny Wu (Geochemistry, Geophysics, Geosystems)
Abstract The slab thermal state model predicts that only cold slabs should retain some of their intra‐slab water beyond subduction zones, while warmer slabs should be nearly dry past the volcanic arc front. Such predictions are yet to be fully tested, as they mostly rely on numerical modeling. To further test the slab thermal model, here we have examined slab‐sensitive elemental and isotopic tracers in recently erupted basalts (<5 Myr) from along and across an arc transect at end‐member types of cold (NE Japan) and hot subduction zones (SW Japan and Ryukyu) and beyond (eastern China intraplate volcanism). We show that the oceanic crust and the incoming hydrated mantle from the cold subducted Pacific plate are the main water carriers beyond subduction zones. Only cold slabs may thus recycle part of their intra‐slab H2O into the lower mantle. Warmer slabs are too dry past the back‐arc or too short‐lived to exert a first order control on deep water recycling.